FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BENIGN PROSTATIC HYPERPLASIA (BPH) - sukron sukron (IKesT Muhammadiyah Palembang, 2022)
Benign prostatic Hyperplasia (BPH) is an enlargement of the gland and cellular tissue of the prostate gland associated with endocrine changes related to the aging process, this condition is thought to be influenced by factors such as age, weight, smoking history, history of consuming drugs that trigger libido, history of diabetes mellitus (DM), cardiac history. The purpose of this study was to determine the factors associated with the incidence of BPH. This study used a quantitative analytical method with a cross sectional approach, this sample was taken using accidental sampling technique. The sample in this study were urological patients who were hospitalized at the surgical IRNA of Dr. Mohammad Hosein Hospital Palembang, totaling 61 respondents with a mean age of 70 years (0.30027). The results of the Chi-squere test showed a significant relationship between age and the incidence of BPH (p= 0.02), there was a relationship between body weight and the incidence of BPH (p=0.007), there was a relationship between smoking history and the incidence of BPH (p= 0.02) , there was a history of consuming libido-triggering drugs with the incidence of BPH (p= 0.05), there was no relationship between a history of diabetes mellitus and the incidence of BPH (p=1.00), there was no significant relationship between a history of heart disease and the incidence of BPH (p= 0.383). It is hoped that nurse practitioners can optimize themselves as educators in providing information about BPH, especially factors related to the incidence of BPH.